Radon retrospective dosimetry in different environments - Giaritzoglou, I.; Aslanoglou, X.; Stamoulis, K. C.; Alexandropoulou, S.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2020)
In the present study of retrospective dosimetry, measurements or Radon (222Rn) and Polonium (210Po) were performed. Radon is a radioactive gas and is concentrated in the interior of residential buildings and working places and is considered as a primary cause of lung cancer. To evaluate measurements in different environments, alpha spectrometry was employed in estimating exposure to radon in various locations over a long period of time (hence, the use of the term “retrospective”) through exposure of plastic and glass surfaces. Following these measurements, the Conversion Factor (CF) was calculated. This factor correlates the measured surface concentrations of 210Po with the 222Rn concentrations in the environments under study.